VISUALIZATION AND MEASUREMENTS OF BUBBLY TWO-PHASE FLOW STRUCTURE USING PARTICLE IMAGING VELOCIMETRY (PIV) - Abdulmouti, Hassan; Jassim, Esam (European Scientific Journal, ESJ, 2013)
Gas injection through a bottom nozzle is very popular and has wide applications. Hence; many researchers have carried out extensive model experiments by focusing on flow field’s structure using air bubbles. The bubble plume, which is a typical form of bubble flow, is known as one of the transport phenomena that have the capability to drive a large-scale convection due to the buoyancy of the bubbles. The technique of using a surface flow generated by the bubble plume is utilized as an effective way to control and collect surface floating substances in naval systems, lakes, seas, rivers, oceans especially the oil layer formed during large oil spill accidents. The surface flows generated by bubble plumes are considered to be key phenomena in various kinds of reactors, engineering processes and industrial processes handling a free surface. The motivation of this research is to broaden the understanding and demonstration of the following points: 1) The most important applications of bubbly flow and gas-liquid two-phase flow. 2) The differences of surface flow generation mechanisms among single-phase liquid jet, single phase buoyant plume, and bubble plume. 3) The relationship between the dominated parameters of bubbly flow that are demanded to describe the characteristics of the bubble generating surface flow. Such flow depends on the gas flow rate, the bubble size, void friction, bubble velocity and the internal two-phase flow structure of the bubble plume. Laboratory experiments have been carried out in order to investigate the multi-dimensional motion of water and bubbles. The data are obtained by applying image processing and Particle Imaging Velocimetry (PIV) measurements to two kinds of visualized images: The first is visualization of the whole field around the bubble plume, and the second is that of the flow structure of bubble for the different sections of bubble regions. The surface flow is effectively generated in case of bubble plume compared to liquid jet flow since the distortion point appears in the vicinity of surface. The flow structure and bubble parameters are sensitively modulated by the gas flow rate and bubble size.